THEORETICAL ASPECTS OF EVALUATION OF CAPITAL ASSETS OF COMPANIES (Marketing Journal, 2025)
This article analyzes the theory of capital asset valuation and its main approaches — Capital Asset Pricing Model (CAPM) and Arbitrage Pricing Theory (APT). The theoretical foundations, methodological approaches, advantages and disadvantages of capital asset valuation are considered in detail. The article presents an analytical comparison of the effectiveness of valuation models using tables and diagrams in terms of risk, market dependence, practical applicability, flexibility and complexity.
Keywords: Capital assets; valuation theory; CAPM; APT; DCF